Beyond traditional training: a comprehensive CIPP evaluation of medical internships: assessing program design, implementation, and clinical competency outcomes - Nooshin Yoshany; Seyed Saeed Mazloomy Mahmoodabad; Leila Moradi; Manoj Sharma (BMC Medical Education)
Abstract Aim Internship programs are important components of teaching and learning that provide medical students with opportunities for real-life learning. The study aimed at evaluating the internship program for students of xxx using the CIPP model (Context, Input, Process, and Product). Materials and methods A cross-sectional descriptive analysis was performed on 305 students and 15 faculty members of xxx. Data were collected using a questionnaire based on the CIPP model that developed by researchers. The internship program was evaluated in four areas: input, context, process and product from the perspective of students and faculty members. The scores obtained for each domain were analyzed using SPSS v.21. Results Context Evaluation: Significant stakeholder discrepancy (p < 0.001): 78% of students reported inadequate environmental needs assessment vs. 35% of faculty 72% students identified goal misalignment with clinical realities vs. 28% faculty. Input Evaluation: No significant difference (p = 0.32): Comparable ratings for resource adequacy (students: 4.1/6, faculty: 4.3/6) Similar perceptions of curriculum design quality. Process Evaluation: Major implementation gaps (p < 0.001): Supervision quality: Students 2.8/6 vs. Faculty 4.7/6 Feedback mechanisms: 65% student dissatisfaction. Product Evaluation: Strong CIPP domain correlations: Context→Input: r = 0.769 (p < 0.001). Context→Process: r = 0.733 (p < 0.001). Context→Product: r = 0.724 (p < 0.001). Conclusions The design and implementation of evaluation programs based on the CIPP model may help improve internship programs and achieve students’ professional competencies. The positive and negative findings in this study should be considered by decision makers and healthcare officials when designing and implementing internship programs. Further longitudinal studies may be required to confirm these findings. Clinical trial number Not applicable.